Post-Transcriptional Regulation Mechanisms of sRNA rnTrpL in S. meliloti and E. coli - Li, Siqi; Justus Liebig University Giessen (My University, 2020)
Ribosome-mediated transcription attenuation is a basic and widespread mechanism for posttranscriptional regulation in bacteria. The liberated attenuator RNAs arising in this process are considered nonfunctional. However, the sRNA rnTrpL, which is released by transcriptional attenuation of the tryptophan (Trp) biosynthesis genes, plays important roles in posttranscriptional regulation. In this work, the trans-acting roles of the sRNA rnTrpL and of the peptide peTrpL encoded by this sRNA in S. meliloti were studied. Additionally, it was shown for the first time, that the corresponding sRNA Ec-rnTrpL in E. coli has important functions in trans.In S. meliloti 2011, rnTrpL is constitutively transcribed and its release is regulated only by attenuation of transcription of the downstream genes. To study the S. meliloti sRNA rnTrpL, a deletion mutant 2011deltatrpL was constructed. Additionally, several other deletion mutants in 2011 and 2011deltatrpL background were constructed. Using these strains and suitable plasmids, systems for IPTG-induced production of the sRNA harboring a recombinant 5´-UTR or of the native-5´-end, leaderless rnTrpL were established. Using these systems for inducible sRNA production, evidence for interaction of the sRNA with several predicted targets was presented, including trpDC, rpoE1 and rplUrpmA. Additionally, role of RNases in the sRNA regulation was studied. Interestingly, the sRNA rnTrpL shows at least two different posttranscriptional regulation mechanisms for its mRNA targets in S. meliloti: an antibiotic-dependent and antibiotic-independent mechanism. The trpDC mRNA, the amount of which is decreased upon rnTrpL induction, is a tetracycline (Tc)-independent target. Its direct base-pairing with rnTrpL was vaildated in vivo using an egfp reporter plasmids. On the other hand, the rplUrpmA mRNA is a Tc-dependent target, but its downregulation additionally depends on the peTrpL peptide encoded by the sRNA. An antisense RNA (asRNA) complementary to rplUrpmA also seems to play a role in this regulation. Transcription induction of this asRNA upon Tc exposure was proven.Furthermore, this work provides evidence for two sRNA-independent targets of the peTrpL peptide in S. meliloti, smeR and phoR. The smeR gene encoding a transcription regulator was investigated. Co-transcription of smeR with the multidrug efflux pump genes smeAB was proven, showing the existence of a smeABR operon, which needs posttranscriptional regulation. In this regulation, the peTrpL peptide seems to work with an asRNA (as-smeR RNA), for which antibiotic-inducible transcription was validated. Alanine scanning mutagenesis revealed that S4, T8 and W12 of the 14 aa peTrpL peptide are necessary for its downregulating effect on both smeR and rplUrpmA, pointing to similar mechnanism operating on both targets. The mRNA targets and the corresponding asRNAs were affected similarly by the alanine scanning mutagenesis. Additionally, this work shows that in Escherichia coli MG1655, the Ec-rnTrpL level is higher in minimal than in rich medium, because without external tryptophan supply, its transcription is derepressed. To study the effect of Ec-rnTrpL on predicted target mRNAs, first a system for inducible sRNA transcription was established. Analysis of mRNA levels after sRNA induction suggested that Ec-rnTrpL is a trans-acting sRNA, which affects dnaA, sanA, rsuAbcr and mcp. Interestingly, the level of the rsuAbcr co-transcript mRNA was decreased by sRNA Ec-rnTrpL overproduction only under Tc exposure. The sRNA base-pairing with rsuAbcr mRNA was validated in vivo. While the physiological importance of rsuAbcr downregulation by Ec-rnTrpL still remains to be uncovered, its role in regulation of dnaA, the gene encoding the master regulator of initiation of chromosome replication, is supported by the presented data. Overexpression and deletion of the Ec-rnTrpL gene decreased and increased the dnaA mRNA levels, respectively. Base pairing between the sRNA and dnaA mRNA in vivo was validated. Furthermore, the oriC level was increased in the deltatrpL mutant, in line with the expected DnaA overproduction and increased initiation of chromosome replication in the absence of Ec-rnTrpL. Moreover, in minimal medium cultures, the the oriC level was increased upon addition of tryptophan in the wild type strain but not in the deltatrpL mutant. The results suggest that Ec-rnTrpL contributes to DnaA homeostasis under conditions of different nutrient availability. They also suggest that in this RNA-based regulation, tryptophan is a signal indicating nutrient availability.Althogether, the presented data show that rnTrpL is a conserved sRNA with own functions in trans in alpha- and in gamma-Proteobacteria. Moreover, the data suggest that in both proteobacterial lineages the rnTrpL sRNA has antibiotic-dependent and antibiotic- independent targets.
Keywords: ddc:570